2021
DOI: 10.3221/igf-esis.58.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gaseous carburizing thermochemical treatment on tribological behavior of Ti–6Al–4V alloy

Abstract: This study, concerns the improvement of the hardness and resistance to wear of the Ti-6Al-4V alloy surface by means of thermochemical treatment, for obtaining coatings on the Ti-6Al-4V alloy gives performance of resistance to wear phenomena. Three-thermochemical treatment time (2h, 4h, and 6h) was chosen for investigation of the effect of such treatment on this alloy. The hardness test under an indentation load of 50 gf with a Vickers pyramidal indenter revealed that the surface hardness is 335 Hv for the untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Coatings 2024, 14, x FOR PEER REVIEW 26 of 42 thickness and the tribological properties of TC4 alloys improve proportionally with increased treatment durations. Upon examining the comparative graph of the tribological properties in Figure 26 [114], a distinct trend is evident. Alloys subjected to prolonged carburization times demonstrate significantly lower friction coefficients.…”
Section: Gas Carburizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Coatings 2024, 14, x FOR PEER REVIEW 26 of 42 thickness and the tribological properties of TC4 alloys improve proportionally with increased treatment durations. Upon examining the comparative graph of the tribological properties in Figure 26 [114], a distinct trend is evident. Alloys subjected to prolonged carburization times demonstrate significantly lower friction coefficients.…”
Section: Gas Carburizationmentioning
confidence: 99%
“…Therefore, longer treatment times typically yield a carburized layer of superior quality. Amar et al [114] observed that the carburized layer's could compromise its mechanical properties. The resultant TiC layer is known for its enhanced hardness and wear resistance, making gas carburizing a vital technique in the surface treatment of titanium alloys.…”
Section: Gas Carburizationmentioning
confidence: 99%
See 2 more Smart Citations